Incidence of phlebitis among adult patients with peripheral intravenous catheter in an east coast hospital Malaysia - Daud, Azlina; Mohamad, Fatimah; Sowtali, Siti Noorkhairina (IIUM Press, 2018)
The insertion of peripheral intravenous catheter is essential among hospitalized patients for treatment purposes. However, this procedure usually fails before the end of therapy due to many complications. One of the most complications occurred is phlebitis. Objective: This study aims to determine the incidence rate of phlebitis among patients with peripheral intravenous catheter. Methods: An observational study was conducted in one of the hospitals in East Coast Malaysia. There were 321 data collected among patients who had peripheral intravenous catheter in medical, gynecology and orthopedic wards. The incidence of phlebitis was evaluated using modified Visual Infusion Phlebitis score checklist. Results: The incidence of phlebitis, was found out to be 36.1% (n=116/321). Most patients who developed phlebitis had visual infusion phlebitis, with a score of two (34.9%) and the rest developed phlebitis with a score of three (1.2%). Conclusion: This high incidence of phlebitis indicated a worrying outcome. Therefore, the study findings suggested that a specific guideline on post insertion management of peripheral intravenous catheter should be revised which may help in reducing more incidence of phlebitis, subsequently reduce infection in ward, and provide more safety environment in hospital and reducing cost in managing infection control.